Safety and Urban Parks: A Geospatial Analysis to Examine Safety Concerns - Dawson, Brita. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Rebecca Shakespeare.; Committee: Justin Hollander.; Keywords: Urban planning, and Geographic information science and geodesy.